Fresamento de topo do Inconel® 718 com ferramentas de metal duro microgrãos - Favero Filho, Antonio (2018)
The development of the cemented carbides is considered to be one of the greatest impulses in the area of cutting tools, along with the creation of high speed steel and the use of coatings. Historically the size of the tungsten carbide grains contained in the hard metals has ranged from 1 to 10 μm, but manufacturers are decreasing these particles to values below 1 μm. This reduction in grain size makes the carbide denser, improving fracture toughness and thus presenting higher cutting edge strength, improving the cutting performance of materials with low machinability. Due to its excellent mechanical properties at high temperatures, Inconel® 718 is widely used in aeronautical, submarine components, as well as other applications where the material to be used needs a combination of refractoriness and resistance to corrosion and wear. This material is also well known for its low machinability, as it presents low loss of mechanical properties with increasing temperature, low thermal conductivity and is work-hardened when subjected to machining efforts. This works compared the performance of two Ceratizit / OSG micrograin milling cutters, TMG30 and CTS18D, in the milling of aged Inconel® 718 with an average hardness of 450 HV. This comparison was performed through work-life tests, surface finish, machining power and machining temperature measurements. It was concluded that for cutting conditions with higher feed rates (0.031 mm/rev.tooth) and high cutting speeds (75 m/min), none of the tested tool classes showed satisfactory life results. However, for the cutting conditions with lower feed rates (0.016 mm/rev.tooth) and lower cutting speed (15 m/min), both tools presented good work-life results, there being no statistical differences between them, possibly due to the small difference in hardness between the tools. The results of temperature and power showed direct correlation with the cutting conditions.